7(x+2)-3(x-8)> 10 3(х-2)-4> = 2(x+3) с полным ходом решения

ZnayNeZnay ZnayNeZnay    1   20.05.2019 01:50    0

Ответы
ghvghbb ghvghbb  13.06.2020 08:25

1)7(x+2)-3(x-8)>10

7x+14-3x+24>10

4x>10-24-14

4x>-28

x>-7

 

2)3(х-2)-4>= 2(x+3)

   3x-6-4=2x+6

3x-2x=6+4+6

x=16

 

ПОКАЗАТЬ ОТВЕТЫ
veshove veshove  13.06.2020 08:25

1) 7(x+2)-3(x-8)> 10

раскрываем скобки

 7x+14-3x+24>10

4x+38>10

4x>-28

x>-7

2)тоже раскрываем скобки 3x-6-4=2x+6

x=16

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра